METHODICAL and PSYCHOLOGICAL POSSIBILITIES FOR RUSSIAN CLASS TEACHERS - Rabbanakulov, Hikmatillo; Norbovayevna, Muratova Shoista; Nurmaxmatovna, Hamraeva Guli (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses Russian language teaching methods, methods, history of Russian origin, predicting the effectiveness of teaching, the proper use of teaching methods, and the necessary teaching tools, other pre-requisites.As is well-known, Russian language is taught in all higher educational institutions, from preschool education institutions to ensuring free communication between the different nationalities living in Uzbekistan.The purpose of this article is, first and foremost, to enable our compatriots to freely communicate not only with their socio-economic topics, but also in their professional field.